(untitled) (Conversatoria Linguistica, 2019)
Metaphors are so profoundly prevalent in human life that very often we do not realize their existence. This lack of the awareness is the reason why we tend to use certain expressions and phrases containing metaphors without a flick. Some metaphoric expressions have rooted so deeply in our language tradition and have become so popular and widespread that it does not pose any problem for us to comprehend them. In the view of that it is very challenging and though provoking to establish if the deaf are capable of processing and understanding common metaphors as well. Can the metaphoric expressions be found in the conceptual framework of the hearing-impaired person? What would be the way to perceive and interpret such expressions?